Research on the interface design of ASD children intervention APP based on Kano-entropy weight method - Zhang, Bingchen; Qi, Yunlin; Yang, Yuling; Zhang, Jiping (Frontiers in Psychiatry, 2025)
BackgroundIn recent years, there has been a notable increase in the prevalence of Autism Spectrum Disorder (ASD) among children in China. To enhance the efficacy of ASD intervention apps and streamline the design process for designers, this study proposes an interface design research method for ASD intervention apps based on the Kano-entropy weight method.MethodsFirst, the basic research process for ASD children is extracted by combining the characteristics of the Kano model and the entropy method. Additionally, representative app samples currently available on the market are collected and organized. Subsequently, the representative needs of ASD children are subjected to analysis and synthesis. Secondly, the data obtained from the questionnaires are organized, and the entropy method is employed to calculate the weight of the need indicators. Subsequently, the characteristics of the intervention apps and the magnitude of the weight values are employed in the analysis of different categories of needs. The case design practice is conducted with a focus on strengthening the effectiveness of the intervention apps from a human-computer interaction perspective, with a particular emphasis on relevant ASD children’s intervention training. The study employs the Kano-entropy weight method to analyze the demand indicators for ASD intervention apps in terms of content, usability, and visual design through survey analysis.ResultsThis study compiled 26 pieces of user demand information, extracted 17 specific indicators, and classified them into three types: content-based, operable, and visual. The interface design of the intervention app focuses on improving emotional abilities. Further enrich the content of the ASD children’s intervention app, improve its operation, enhance visual appeal, provide reference and basis for subsequent related designs, and improve the effectiveness of intervention training.ConclusionsThe objective is to enhance the efficacy of the apps from the perspective of human-computer interaction. This endeavor seeks to furnish pertinent theoretical references for the design of navigation interfaces for intervention apps and to provide effective assistance to educators and designers.